Policy-Making and Systemic Complexity - Bedau, Mark A. (The Hastings Center report, 2014)
Synthetic biology has spawned a debate about how society and the international community should go about policy-making, especially given the potential for both transformative benefits and existential threats. One of the significant contributions of “The Ethics of Synthetic Biology: Next Steps and Prior Questions,” by Kaebnick, Gusmano, and Murray, is its exploration of the difficulties of developing policy that appropriately addresses the risks and benefits of synthetic biology. In this comment I want to develop this point further and emphasize how the proper methodology for addressing synthetic biology's ethical and public policy issues are affected by the unpredictable and complex causal webs in synthetic biology (which have analogs in other new and emerging technologies).